The Integration Interests of Ukraine: the European Union or Customs Union - Lymar, V.V. (Економічний вісник Донбасу, 2013)
The article is devoted to the problems and prospects of Ukrainian economy development as a result of free trade area creating with the EU and integration to the Customs Union. The geographic and goods structure of the international trade are analyzed and it is made the conclusion about the strategic importance of post-Soviet area market for the Ukrainian economy.